Critique of Medical Perspective on the Beginning of Human Person Based on Biblical and Biological Insights - Harsono, Ferriandis (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2022)
Many people and (Catholic) medical practitioners use or provide all kinds of contraceptives, including those that work by preventing implantation of zygote. Some medical experts affirm that preventing implantation of zygote is not an abortion because before the implantation, zygote is not considered as human person and does not have basic rights to live as human person. However, the Catholic Church affirms that human life must be respected and given the basic rights to live as human person since the conception. The difference between medical experts and the Catholic Church results from the different perspectives on the time of the beginning of human person. Both medical experts and the Catholic Church agree that human life begins at the time of conception, but they do not agree that human person begins at the time of conception. Many medical experts say that after the conception and before the implantation, zygote can split into identical twins so that human personhood cannot be determined before the implantation. In this article, the medical perspective will be criticized using biblical and biological insights. These insights may enlighten us that preventing an implantation of zygote is an abortion because zygote is already a human person.